The Role of a Facilitator in Co-Design Applications for Exploratory Analysis in Domains of High Complexity: The Case of MAHiCGO - Talar B. Yacoubian (16896378) (2021)
Background Robust and useful tools for exploratory analysis in biosciences are still lagging behind the size and complexity of the biological datasets produced since the completion of the human genome in 2000. A possible reason is that developers are unlikely to understand domain and case-specific requirements of existing research questions. Methods We formed a design team comprising a visualization expert, a Human Computer Interaction (HCI) researcher, bioinformatics domain experts, and the Principal Investigator (PI) as a `facilitator' filling the communication gap between them. We implemented co-design methodology. Results We identified the need for an interactive visual analytic tool for exploratory analysis of biological data. We describe the process of developing MAHiCGO, a novel tool for the simultaneous visualization of MA Gene Expression data, Hi-C data and Gene Ontology (GO) information in an interactive manner for the exploratory analysis of biological data. Conclusion The key finding of this research to include a facilitator role in the co-design is useful in the evolving fields of design research and of bioinformatics, merging computational sciences with biosciences. The findings support in understanding new functional roles in the field of design, in particular design of computer applications in highly complex domains such as bioinformatics, and for highly complex tasks such as exploratory tasks. The findings also stress on the key role of visualization to expand user cognitive capabilities, and of co-design for constant engagement of domain experts in the creation process. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2021.3063468